2007
DOI: 10.1586/1744666x.3.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: the complications of immune dysfunction

Abstract: Hepatitis C virus (HCV) infection has been linked to numerous diseases of immune dysfunction, including, but not limited to, essential mixed cryoglobulinemia and non-Hodgkin's lymphoma. Clinical studies support these associations and treatment of the underlying HCV infection has been variably successful. Recent studies, focusing on the role of HCV gene products, have discovered evidence of dysregulated responses in multiple aspects of host immunity that may be contributing to the genesis of these diseases. Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 103 publications
0
16
0
Order By: Relevance
“…8,23 In this study, we found that the nucleocapsid core protein of HCV differentially regulates the functions of both B-and T-lymphocytes. This involved regulation of lymphocyte activation markers, effects on measures of cellular activation and alteration in adapter and kinase pathways fundamental to lymphocyte function.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…8,23 In this study, we found that the nucleocapsid core protein of HCV differentially regulates the functions of both B-and T-lymphocytes. This involved regulation of lymphocyte activation markers, effects on measures of cellular activation and alteration in adapter and kinase pathways fundamental to lymphocyte function.…”
Section: Discussionmentioning
confidence: 63%
“…This is manifest in several ways, including aberrant B-cell proliferation, decreased threshold for B-cell activation via the B-cell receptor complex, and overproduction of antibodies that are ineffective in controlling viral infection. 8 A non-neoplastic expansion of B-cell clones expressing immunoglobulin M (IgM) has been noted in mixed cryoglobulinemia, a process that can be observed in more than 50% of individuals chronically infected with HCV. It appears that whereas T-cell function is suppressed during chronic HCV infection, B cells often exhibit activation and clonal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior studies, the most common non-AIDS-defining infection in our study was bacterial pneumonia 2426 . Chronic viral hepatitis is known to be associated with dysregulation of hepatitis-specific immune responses, but further investigation is needed to explore potential mechanisms underlying an increased risk of bacterial infections 27,28 . Preventable infections such as influenza and pneumococcal pneumonia should be proactively addressed in PLWH with appropriate vaccinations to potentially reduce morbidity and hospitalizations 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infects over 180 million people worldwide and exhibits a remarkable propensity toward chronic hepatitis, liver cirrhosis and hepatocellular carcinoma1. Chronic HCV infection is also associated with B cell lymphoproliferative disorders2, including most notably mixed cryoglobulinemia (MC) and B cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%